APB featured expertise: Dr. Rozaimah Rashidin, Department of Malay Studies - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Dr Rozaimah Rashidin is a senior lecturer in the Department of Malay Studies, Akademi Pengajian Bahasa, UITM Shah Alam. She began her career journey in UITM in 2007 and specialises in Semantics and Pragmatics. She is also the Head of Study Center (KPP) for the LG241 Program (Bachelor of Language Studies (Applied) Malay for Professional Communication). She holds a Bachelor of Arts (Honours), a Masters for Social Science (Linguistics) in 2007 and a Doctorate in Philosophy (Linguistics) in 2016 from Universiti Kebangsaan Malaysia. Dr Rozaimah Rashidin also holds a Diploma in Professional Translation (Mass Communication) from the Persatuan Penterjemah Malaysia (PPM) and Dewan Bahasa dan Pustaka (DBP).